The review process in tourism academia: An elaboration of reviewers' extrinsic and intrinsic motivations - Correia, Antónia (2019)
The process of review is one of the most powerful influences in social sciences. But this process may have either a positive or negative impact on the quality of research outputs. The broader discussion about the paths to develop research surprisingly does not include the understanding of reviewers' and editors' procedures, which are the lifeblood of the system. This paper provides an analysis of the review process through the perspective of reviewers and editors. A mixed method approach was used to assess the motivations, goals and intentions of reviewers to keep collaborating with tourism research. Results suggest that, even under pressure, reviewers are willing to contribute in a positive way, though the added value of this duty is decreasing. Editors are aware of this evidence although they keep trying to push reviewers to deliver qualified contributions. Overall this process seems to be fed by the sense of belonging to the tourism academic community. This community is small but strong enough to keep the wheel turning. Finally, the research suggests the ways in which the review process can be improved to ensure its quality. (C) 2017 The Authors.